Management of blunt traumatic abdominal wall hernias: A Western Trauma Association multicenter study. Issue 5 (November 2021) - Harrell, Kevin N.; Grimes, Arthur D.; Albrecht, Roxie M.; Reynolds, Jessica K.; Ueland, Walker R.; Sciarretta, Jason D.; Todd, Samual R.; Trust, Marc D.; Ngoue, Marielle; Thomas, Bradley W.; Ayuso, Sullivan A.; LaRiccia, Aimee; et al.
Abstract : BACKGROUND: Blunt traumatic abdominal wall hernias (TAWH) occur in approximately 15, 000 patients per year. Limited data are available to guide the timing of surgical intervention or the feasibility of nonoperative management. METHODS: A retrospective study of patients presenting with blunt TAWH from January 2012 through December 2018 was conducted. Patient demographic, surgical, and outcomes data were collected from 20 institutions through the Western Trauma Association Multicenter Trials Committee. RESULTS: Two hundred and eighty-one patients with TAWH were identified. One hundred and seventy-six (62.6%) patients underwent operative hernia repair, and 105 (37.4%) patients underwent nonoperative management. Of those undergoing surgical intervention, 157 (89.3%) were repaired during the index hospitalization, and 19 (10.7%) underwent delayed repair. Bowel injury was identified in 95 (33.8%) patients with the majority occurring with rectus and flank hernias (82.1%) as compared with lumbar hernias (15.8%). Overall hernia recurrence rate was 12.0% (n = 21). Nonoperative patients had a higher Injury Severity Score (24.4 vs. 19.4, p = 0.010), head Abbreviated Injury Scale score (1.1 vs. 0.6, p = 0.006), and mortality rate (11.4% vs. 4.0%, p = 0.031). Patients who underwent late repair had lower rates of primary fascial repair (46.4% vs. 77.1%, p = 0.012) and higher rates of mesh use (78.9% vs. 32.5%, p < 0.001). Recurrence rate was not statistically different between the late and early repair groups (15.8% vs. 11.5%, p = 0.869). CONCLUSION: This report is the largest series and first multicenter study to investigate TAWHs. Bowel injury was identified in over 30% of TAWH cases indicating a significant need for immediate laparotomy. In other cases, operative management may be deferred in specific patients with other life-threatening injuries, or in stable patients with concern for bowel injury. Hernia recurrence was not different between the late and early repair groups. LEVEL OF EVIDENCE: Therapeutic/care management, Level IV.